Does the composition of polystyrene trays affect Candida spp. biofilm formation?. (6th September 2018) - Díaz-García, Judith; Marcos-Zambrano, Laura Judith; Muñoz, Patricia; Guinea, Jesús; Escribano, Pilar
Abstract: The biofilm formation ability of Candida species seems to have a role in the prognosis of patients with candidemia. Biofilm formation is usually tested using 96 well flat bottom polystyrene microtiter plates, although the type of plastic used is not commonly reported. This study compares biofilm formation by Candida spp. on six types of plates from three brands (three non-tissue-treated and three tissue-treated). Thirty isolates of each of the following species were selected: C. albicans, C. parapsilosis, C. glabrata, C. tropicalis, as well as 15 isolates of C. krusei ( n = 135 isolates) from patients with candidemia. Biofilm production was evaluated by measuring biomass production and metabolic activity. Our results show higher biomass production and metabolic activity of biofilms formed on non-tissue-treated plates in comparison to those formed on tissue-treated plates ( P < .001). We only found significant differences in metabolic activity of biofilms formed on non-tissue-treated plates ( P < .003). All comparisons including biofilm formation and metabolic activity among plates of the same brand yielded higher biofilm formation on non-treated plates compared to treated plates ( P < .001). Significant difference in biomass production by C. parapsilosis was only seen when comparing between the various tissue-treated plastics ( P < .03). In contrast, comparisons of different non-tissue-treated tray brands yielded significant metabolic activity differences for all species except for C. parapsilosis ( P < .05). Biofilm formation and metabolic activity is significantly affected by the plastic composition of non-tissue-treated trays leading to increased biofilm formation.